2014
DOI: 10.1155/2014/452892
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Cytotoxic Effects of CAM Therapies: AnIn VitroStudy in Normal Kidney Cell Lines

Abstract: The purpose of this current study was to justify the incorporation of complementary and alternate medicine (CAM) in current cancer treatments. The major drawback of anticancer drugs is their nonselective killing, which ultimately leads to attrition of normal cells. Keeping this as the foundation of our study, we made an effort to compare the cytotoxicity associated with a known chemotherapeutic drug 5-Fluorouracil (5-FU), with certain CAM therapies previously reported to have anticancer activity. The parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…A recently published study showed alcohol and aqueous extracts of wheatgrass to be less damaging than 5-FU to normal kidney epithelial cells, thereby confirming the safety of these extracts in anti-cancer uses [44].…”
Section: Wheatgrass Derivatives Combined With Cancer Drugsmentioning
confidence: 73%
“…A recently published study showed alcohol and aqueous extracts of wheatgrass to be less damaging than 5-FU to normal kidney epithelial cells, thereby confirming the safety of these extracts in anti-cancer uses [44].…”
Section: Wheatgrass Derivatives Combined With Cancer Drugsmentioning
confidence: 73%
“…25 However a study on normal monkey kidney cell line, in vitro, showed that it is non-toxic to normal cells. 26 Carcinosinum, the potentized preparations from carcinomas and has been used against malignant conditions, was also subjected to various scientific studies. It was reported that Carcinosinum 200c could induce apoptosis in DLA cells in vitro, mediated through the upregulation of p53 gene.…”
Section: Introductionmentioning
confidence: 99%
“…Things to do when macrofungi were found are: documented with a camera from various sides (attachment on the substrate, the top side, besides, the bottom side, and divided fruiting body). Notes of the primary data or morphology characteristics were collected on the field (type of fungus in general; Pileus: surface color, bruise color, flesh color, surface texture, surface condition, shape, margin; Lamellae: color, type of margin, coloring type, attachment, hymenium type, number of lamellulae, pore shape if any; Stipe: color, bruise color, flesh color, attachment to pileus, surface type, base type; Ornamentations: volva type, annulus type; and color of spore print), Morphometric (Pileus: diameter, height, flesh thickness; Stipe: length, apex diameter, middle diameter, base diameter; Lamellae: depth, length of the tube if any), and secondary data, environmental conditions in which it grows (the condition of the substrate and the surrounding vegetation) (Arora 1986;Foster 2004;Laessøe 2013;Largent 1986). Measurements were also performed on the physical condition of the environment in which it grows (coordinates, altitude, humidity, temperature and light intensity).…”
Section: Field Data Collectionmentioning
confidence: 99%
“…The documentation process was repeated in the laboratory for fruiting bodies of macrofungi from all sides (top, side, bottom, divided fruiting body). Morphological characteristics and morphometric were also checked for the second time (type of fungus in general; Pileus: surface color, bruise color, flesh color, surface texture, surface condition, shape, margin diameter, height, flesh thickness, length, apex diameter, middle diameter, base diameter; Lamellae: color, type of margin, coloring type, attachment, hymenium type, number of lamellulae, pore shape if any, depth, length of the tube if any; Stipe: color, bruise color, flesh color, attachment to pileus, surface type, base type; Ornamentations: volva type, type annulus; and color of spore print) from the fruiting bodies that have been collected (Arora 1986;Foster 2004;Laessøe 2013;Largent 1986).…”
Section: Laboratory Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation